P297 Lung-function profile before and after the first moderate to severe exacerbation during the wisdom study. (15th November 2016) - Wouters, E; Magnussen, H; Rodriguez-Roisin, R; Tetzlaff, K; Bell, S; Calverley, PM A
Abstract : Rationale: The WISDOM study (NCT00975195 ) showed no increased risk of exacerbation when inhaled corticosteroid (ICS) was withdrawn stepwise in patients with severe COPD on LAMA+LABA maintenance therapy versus continued LAMA+LABA+ICS. 1 Daily home spirometry measured the time course of lung-function changes throughout the study. The aim of this post hoc analysis was to address the lung-function profile leading up to, during and following the first moderate-to-severe exacerbation. Methods: WISDOM was a multinational, randomised, double-blind study. 1 Patients with severe to very severe COPD entered a 6-week run-in with LAMA+LABA+ICS (tiotropium 18 µg once daily; salmeterol 50 µg twice daily; fluticasone propionate 500 µg twice daily), and were randomised to continue LAMA+LABA+ICS or salmeterol/tiotropium for 52 weeks while discontinuing ICS in a stepwise manner over 12 weeks. On-treatment daily forced expiratory volume in 1 second (FEV1 ) change from baseline was calculated before and after the first moderate-to-severe exacerbation. In this post hoc analysis, we included patients who experienced a moderate-to-severe exacerbation after the ICS-withdrawal visit, did not have an exacerbation in the 8 weeks before or after the exacerbation, and had daily home-measured FEV1 data available for every week analysed. Results: Of 2488 patients, 262 experienced a moderate-to-severe exacerbation after the ICS-withdrawal visit and had lung-function data for every week. For all patients combined (ICS and ICS withdrawal), change in FEV1 remained relatively stable 56–14 days before the first moderate-to-severe exacerbation (mean FEV1 change from baseline values: −0.04 to −0.07 L) (Figure ). There was a decline in lung function starting 2–3 weeks before exacerbation (FEV1 change value of −0.12 L from baseline), followed by a moderate improvement over ∼14 days. Post-exacerbation lung function did not reach pre-exacerbation levels. Conclusions: Lung function was relatively stable in both treatment groups. Home spirometry measurements showed a marked decline in FEV1 prior to moderate-to-severe exacerbation with improvements seen post-exacerbation, although not to pre-exacerbation levels. These findings support the usefulness of home spirometry to predict exacerbations and to indicate subsequent worsening of lung function resulting from a previous COPD exacerbation. Funding: Boehringer Ingelheim. Please refer to page A273 for declarations of interest in relation to abstract P297. Reference: Magnussen H, et al . N Engl J Med 2014;371 :1285–1294.